Comparative analysis of stable matching algorithms for intelligent work planning of IT teams - Rohovyi, M.; Grinchenko, M. (ХНУРЕ, 2024)
The article is devoted to a comparative analysis of stable mapping algorithms for intelligent planning of work of IT teams working according to agile development methodologies. The authors consider the problem of effective task distribution between developers as a problem of finding stable mapping. The paper presents an overview of existing approaches to task distribution in project teams and justifies the relevance of studying stable mapping algorithms in this context. A research methodology is proposed, which includes the creation of a simulation environment for modeling the task distribution process, synthetic data generation, implementation and evaluation of five key algorithms: SOSM, EADAM, MESMA, RSD and TTC. The purpose of the study is to formulate recommendations for the implementation of stable mapping algorithms for planning and task distribution in IT teams using agile project management methodologies. According to the results of the experiments, the EADAM and SOSM algorithms are recommended for practical application due to their balance of stability, efficiency and satisfaction of performers. Стаття присвячена порівняльному аналізу алгоритмів стабільного зіставлення для інтелектуального планування роботи ІТ-команд, що працюють за гнучкими методологіями розробки. Автори розглядають проблему ефективного розподілу завдань між розробниками як задачу знаходження стабільного зіставлення. У роботі представлено огляд існуючих підходів до розподілу завдань у проєктних командах та обґрунтовано актуальність дослідження алгоритмів стабільного зіставлення в цьому контексті. Запропоновано методологію дослідження, що включає створення симуляційного середовища для моделювання процесу розподілу завдань, генерацію синтетичних даних, реалізацію та оцінку п'яти ключових алгоритмів: SOSM, EADAM, MESMA, RSD та TTC. Метою дослідження є формування рекомендацій щодо імплементації алгоритмів стабільного зіставлення для планування та розподілу задач в ІТ-командах, що використовують гнучкі методології управління проєктами. За результатами проведених експериментів алгоритми EADAM та SOSM рекомендовані для практичного застосування через їх баланс стабільності, ефективності та задоволення виконавців.
Keywords: task distribution; stable comparison algorithms; IT team; flexible development methodologies; project management; розподіл завдань; алгоритми стабільного зіставлення; IT-команда; гнучкі методології розробки; управління проектами